Cross-talk between non-coding RNAs and PI3K/AKT/mTOR pathway in colorectal cancer - Moafian, Zeinab; Maghrouni, Abolfazl; Soltani, Arash; Hashemy, Seyed Isaac (Molecular biology reports, 2021)
Colorectal cancer (CRC) is the third commonest cancer globally, with metastasis being the reason for cancer-associated mortality. Much is still unknown biochemically about CRC, and with current treatments that are not wholly effective over time, new therapeutics are urgently needed. Emerging evidence has shown the importance of non-coding RNAs such as lncRNAs and miRNAs functions in the development and progression of CRC. However, the exact underlying mechanism of these types of RNAs in CRC is still mostly unknown. PI3K/AKT/mTOR pathway contributes to many cellular processes, and dysregulation of this pathway frequently occurs in cancers. In this review, the authors have mostly focused on the significant non-coding RNAs regulators of the PI3K/AKT/mTOR pathway and their contribution to the development or inhibition of CRC and their potential as diagnostic or therapeutic targets in CRC treatment.